2017
DOI: 10.1038/s41598-017-14938-0
|View full text |Cite
|
Sign up to set email alerts
|

Increased synthesis and deposition of extracellular matrix proteins leads to endoplasmic reticulum stress in the trabecular meshwork

Abstract: Increased synthesis and deposition of extracellular matrix (ECM) proteins in the trabecular meshwork (TM) is associated with TM dysfunction and intraocular pressure (IOP) elevation in glaucoma. However, it is not understood how ECM accumulation leads to TM dysfunction and IOP elevation. Using a mouse model of glucocorticoid (GC)-induced glaucoma, primary human TM cells and human post-mortem TM tissues, we show that increased ECM accumulation leads to endoplasmic reticulum (ER) stress in the TM. The potent GC, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
74
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(82 citation statements)
references
References 61 publications
(68 reference statements)
7
74
0
1
Order By: Relevance
“…40,41 In this study it was shown in a human lens 3D model for the first time a clear induction of EMT by glucocorticoid treatment at clinically relevant concentrations. The data are well in line with other studies in the eye showing induction of EMT by a-SMA of, for example, the trabecular mesh 42 and gives further evidence that there is a mechanistic link between PSC and PCO in humans. This might further explain why PCO is more frequent with patients who underwent cataract surgery after drug-induced PSC.…”
Section: Human 3d Lens Spheroid Model 61supporting
confidence: 91%
“…40,41 In this study it was shown in a human lens 3D model for the first time a clear induction of EMT by glucocorticoid treatment at clinically relevant concentrations. The data are well in line with other studies in the eye showing induction of EMT by a-SMA of, for example, the trabecular mesh 42 and gives further evidence that there is a mechanistic link between PSC and PCO in humans. This might further explain why PCO is more frequent with patients who underwent cataract surgery after drug-induced PSC.…”
Section: Human 3d Lens Spheroid Model 61supporting
confidence: 91%
“…Importantly, the IOP in two patients increased only during the administration of dexamethasone (10 mg/m 2 ) and not during the administration of prednisolone (60 mg/m 2 ). Dexamethasone increases the secretory protein load of extracellular matrix proteins in the endoplasmic reticulum (ER) of trabecular meshwork cells, thereby inducing chronic ER stress 10 and promoting ocular hypertension via the transforming growth factor 2 signaling. 11 In the current study, IOP of younger patients with ALL was higher than those who were > 10 years.…”
Section: Discussionmentioning
confidence: 99%
“…We recently demonstrated that Dex-induced intracellular fibronectin and type I collagen interact and co-localize with KDEL antibody, which recognizes the ER stress markers GRP78 and GRP94 (44). Here, we examined whether inhibition of TGF␤ signaling prevents Dex-induced co-localization of fibronectin and type I collagen with KDEL in primary human TM cells (Fig.…”
Section: Inhibition Of Tgf␤ Signaling Reduces Dex-induced Ecm Accumulmentioning
confidence: 99%